The process of developing suicidal thoughts among adolescents: The social and psychological impact according to a national survey in Palestine after the Covid-19 pandemic - Abu dalu, AbedElrahman Maher (Journal of Educational and Psychological Sciences, 2025)
This study aimed to analyze the psychological and social factors associated with the development of suicidal ideation among Palestinian adolescents in the aftermath of the COVID-19 pandemic, and to propose a descriptive model explaining this phenomenon within the local context. A quantitative, descriptive-analytical methodology was employed, based on a nationally representative face-to-face survey conducted with a sample of 4, 288 high school students. The participants were selected using a two-stage stratified cluster sampling technique, covering five geographical regions in Palestine (Northwest, Northeast, Central, South). Data were analyzed using multiple correspondence analysis and logistic regression to explore the relationship between demographic, social, and psychological variables and suicidal ideation. The results revealed a strong correlation between deteriorating mental health and the presence of suicidal thoughts; however, this relationship was mediated by social and structural factors such as personal relationships and family dynamics. The study recommends enhancing psychosocial support for adolescents, implementing preventive programs in schools targeting at-risk groups, and strengthening the roles of families and educational institutions in monitoring mental health.
Keywords: Suicidal ideation; Adolescents; Mental health; Social impact